An Overview of Creative Placemaking as an Enabler for a Sustainable Urban Regeneration - Ramli, Nurul Atikah; Ujang, Norsidah (Environment-Behaviour Proceedings Journal, 2020)
As the rapid growth of cities continues to pose a significant threat to the well-being of people, its adverse effects have moved to the forefront of social sustainability. Urban regeneration has become one of the adaptations in solving a social issue. Alongside these interventions, creative placemaking emerges as an evolving field of practice driving a broader agenda for growth and transformation of cities. This paper reviews the concept of creative placemaking as an approach to urban regeneration and theories extracted from planning and urban design literature. The findings provide an understanding of the significant function of social attributes of place in crafting strategies in the creation of successful creative placemaking. Keywords: Urban regeneration; Creative placemaking; Urban places; Social sustainability eISSN: 2398-4287 Â© 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v5i13.2056